USES OF WILDLIFE IN THE COLOMBIAN AMAZON TRAPEZE AND CONTRIBUTIONS TOWARDS ITS INTEGRAL MANAGEMENT IN THE AMAZON DEPARTMENT - HERNÁNDEZ CORONADO, Astrid Fernanda (2018)
The different wildlife uses were identified in nine rural localities (indigenous communities and settlers) located in the Colombian Amazonian Trapeze, from the application of 239 semi-structured interviews. The species most used and most hunting pressure through their food experiences, magic-religious, and customs are presented. In total, we identified 73 species of wildlife (35 of mammals, 23 of birds, 11 of reptilian, 2 of coleoptera and 1 of gastropod). The main use of wildlife is feeding, followed by medicinal use and as pets. Parts of animals are used for magic-religious activities, crafts, musical instruments, tools and costumes. It as final product develops a proposal of management of wildlife for the Amazonian trapezium.